Kinky Europe: Evidence from the Regional Phillips Curve in the Euro Area - Marius Faber; Gabriel Züllig (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We estimate the slope of the Phillips curve in the euro area, allowing for nonlinearities – or kinks – in the relationship between labor market slack and inflation. We exploit cross-country variation in labor market conditions in the period 2001–2024, absorbing aggregate shocks and endogenous monetary policy reactions with time fixed effects. We find that, while the Phillips curve is usually quite flat, it becomes at least three times steeper when the labor market is sufficiently tight. This kink is more pronounced in the euro area than in the United States, potentially due to more rigid labor markets. Our estimates suggest, however, that despite this nonlinearity, most of the post-pandemic inflation surge is attributable to factors other than labor market tightness.
Keywords: E30; 330; Phillips curve; inflation; nonlinearities